Method for rapidly measuring content of effective alkali in mineral admixture for concrete
The ion selection electrode method combined with the dissolution characteristics of alkali metal ions under specific environmental conditions can be quickly measured, which solves the problem that is difficult to accurately determine in the prior art, and effectively supports concrete quality control and resource utilization of new blends.
Patent Information
- Application Number
- CN202411673855.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-07
AI Technical Summary
It is difficult for the prior art to quickly and accurately determine the effective alkali content in concrete mineral blends, resulting in the contradiction between concrete quality control and the resource utilization of new blends.
The ion-selective electrode method is used to combine the dissolution characteristics of alkali metal ions under specific environmental conditions, and the potassium and sodium content of the leaching liquid is determined quickly to evaluate the effective alkali content in the blend.
It achieves rapid and simple determination of the effective alkali content of mineral blends, reduces the risks of concrete cracking and expansion, and provides a basis for selecting suitable blends in engineering applications.
Smart Images

Figure CN119574677A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a method for quickly determining the effective alkali content in mineral admixtures for concrete. Background Art
[0002] As admixture technology becomes a necessary means for preparing high-performance concrete, its dosage in concrete is increasing. For durability considerations, alkali content is regarded as one of the important technical indicators. The alkali content here refers to the sum of alkalis in various forms (i.e., total alkali content), calculated as equivalent sodium oxide. Since mineral admixtures can usually reduce the alkalinity of pore solution, when preparing concrete with conventional mineral admixtures such as fly ash, an effective ratio is usually taken to control the total alkali content of concrete. For example, the effective alkali content of fly ash is 1 / 6 of the total alkali content, and that of mineral powder and silica fume is 1 / 2 of the total alkali content.
[0003] In order to ensure the quality of concrete, actual projects strictly control the total alkali content of concrete. However, with the increasing amount of admixtures, and in the context of sustainable development and resource utilization of solid waste, new admixtures continue to emerge. However, the industry's understanding of various new admixtures is not as good as conventional admixtures such as fly ash, and the research foundation is weak. When the total alkali content of admixtures is included in concrete, it always exceeds the limit regulations on the total alkali content of concrete. The requirements for resource utilization of new admixtures are inconsistent with concrete quality control, and the alkali in the admixtures begins to gradually restrict the development of concrete. In actual projects, it always happens that even if the specification restrictions are exceeded, potential alkali-aggregate reaction or severe shrinkage does not occur. There are contradictions between engineering practice results and total alkali control guidance in different regions, which restricts the development of solid waste resource utilization and concrete technology.
[0004] At present, the reference cement chemical analysis method is adopted to obtain the alkaline solution through acid dissolution, and the sodium and potassium content is determined by chemical analysis methods (flame photometry, AAS), or ICP, XRF and other elemental analysis methods are used to determine the sodium and potassium content. The chemical analysis method determines the total Na and K content in the solution, while ignoring the various interaction forces between components. These complex interactions between particles result in not all alkali elements participating in the reaction; ICP and XRF are used to directly determine the Na and K content in the solid sample, that is, the total alkali content of the sample. In fact, the effective alkali content of mineral admixtures during the hydration process does not completely correspond to the water-soluble alkali or the total alkali content. For example Figure 1As shown in Figure 1, the effective alkali of admixture refers to the part of alkali present in the pore solution after secondary hydration release and absorption when hydrated to a certain age. It is generally believed that only this part of alkali participates in various reactions in concrete. The elemental analysis method not only overestimates the effective alkali in admixtures that can actually participate in affecting the long-term performance and durability of concrete, but also the required equipment is not suitable for on-site laboratory applications. Therefore, a method for quickly determining the effective alkali content in mineral admixtures is needed.
[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for quickly determining the effective alkali content in mineral admixtures for concrete.
[0007] The effect of alkali on concrete is to study the part of Na that can actually participate in the reaction. + , K + , while activity is the effective concentration that reflects the action of ions in the solution, and can more accurately reflect the contribution of alkaline substances that cause reactions in actual solutions. In addition, the existing elemental determination methods are usually time-consuming and complicated to operate, which is not conducive to rapid on-site determination. Therefore, rapid and accurate determination of the effective alkali content in admixtures is of great significance for the optimal design and use of concrete materials.
[0008] Although the activity and activity coefficient cannot be calculated and inferred from a thermodynamic point of view for the time being, after introducing the ion activity to define the effective base, the ion selective electrode can be used to determine the effective base in the admixture, and this function can be achieved by utilizing the Nernst response principle of ions under the action of electric potential.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A method for quickly determining the effective alkali content in a mineral admixture for concrete comprises the following steps:
[0011] S1. Sample preparation: Prepare the mineral admixture sample and seal it after grinding and sieving. Before analysis, dry the sample to constant weight and cool it to room temperature for later use;
[0012] S2. Preparation of leaching solution: Prepare the slurry with the sample to be tested, the reference cement and water in a mass ratio of 5:2:10, and after curing for 28 days, grind, dilute and filter to obtain the leaching solution; the mineral admixture is mixed with cement and soaked in water, and the soluble alkali metal ions in the mineral are gradually released into the leaching solution by standing, sealing and under specific temperature conditions (38±2℃). The high temperature and humid environment accelerates the dissolution of alkali ions, allowing the effective alkali content to be quickly evaluated in a short period of time;
[0013] S3. Determination of potassium and sodium content: Determine the concentration of potassium and sodium alkali ions in the extract by ion selective electrode method;
[0014] S4. Calculation of results and determination of effective alkali: The measured alkali ion concentration is converted into the effective alkali content in the admixture, and finally the Na 2 Na2O equivalent (%). Na2O equivalent is a unified effective alkali content index, which is convenient for comparing and evaluating the alkali content of different admixtures. 2 The calculation formula of O equivalent combines Na + and K + The molar ratio relationship of the two groups is obtained, thereby obtaining a standardized result reflecting the alkali content of the sample.
[0015] Among them, the test water should not be lower than the requirements of Grade 3 water specified in "Specifications and Test Methods for Water in Analytical Laboratories" GB / T 6682.
[0016] Preferably, step S1 specifically includes:
[0017] S11: Prepare the mineral admixture sample in proportion, use the quartering method or a divider to reduce the sample to twice the prepared mass, and then sieve it through an 80μm square hole sieve to ensure the uniformity of the sample;
[0018] S12: Use a magnet to remove metallic iron from the sieve residue, and grind the sieve residue again so that it all passes through a square hole sieve with a pore size of 80μm to ensure uniformity; using a magnet to remove metallic iron impurities from the sieve residue can effectively eliminate the interference of metal impurities in the determination of alkali content, especially in the subsequent steps, when the alkali ion concentration is determined by an ion selective electrode, it can avoid errors caused by metal interference, thereby improving the accuracy of the measurement.
[0019] S13: Store the evenly ground sample in a sealed bottle; this can prevent moisture or other impurities in the external environment from contaminating the sample, ensure that the sample composition remains stable, and thus improve the reliability of the experiment.
[0020] S14: Before the sample is analyzed, it is dried in an oven at (105±5)℃ to constant weight, and then placed in a desiccator to cool to room temperature for use. This can avoid the influence of different moisture contents on the measurement results. After drying, it is cooled to room temperature in a desiccator to prevent the sample from absorbing moisture in the air, ensuring that the sample is in a dry and stable state during the measurement process, thereby improving the accuracy of the analysis results.
[0021] The present invention can reduce the inhomogeneity between samples to the greatest extent by reducing and screening the samples, ensure the representativeness of each component in the samples, and improve the repeatability of the analysis process and the reliability of the results. The sieve residue is repeatedly ground and ensured to pass through the sieve, which reduces the deviation in the determination of alkali content that may be caused by the difference in particle size, making the test samples more standardized.
[0022] Preferably, step S2 specifically includes:
[0023] S21: Weigh the test sample and reference cement in a mass ratio of 5:2, accurately record the sample mass to 0.0001g, mix them evenly and put them into the experimental bottle;
[0024] S22: Add water twice the mass of the test sample into the experimental bottle, seal the bottle mouth and shake it evenly. After standing for a while and a supernatant appears, gently rotate the experimental bottle to ensure that there is no residue on the bottle wall. This can ensure that all mineral admixtures participate in the reaction, avoid insufficient or uneven sample reaction due to residue, reduce experimental errors, and thus improve the reliability of the measurement results.
[0025] S23: Seal the test bottle, place it in a sealed container filled with water at the bottom, and then leave it at 38±2℃ for 28 days; this simulates the dissolution process of admixtures in a hot and humid environment and accelerates the release of alkali ions in minerals. This temperature condition accelerates the dissolution of alkali by simulating a similar alkali diffusion environment in concrete, shortens the measurement cycle, and ensures that the results are representative and stable. The choice of this temperature (38±2℃) helps to stabilize the ion dissolution and improve the controllability of the dissolution process.
[0026] S24: After 28 days, open the experimental bottle and transfer the entire contents to a mortar and grind into a uniform slurry, then transfer to a beaker, add water to dilute, and stir for 1 hour; ensure that all solid components are fully in contact with water, which helps to completely dissolve the effective alkali ions. The grinding process increases the contact area between the sample and the solvent, which helps to increase the speed and amount of ion release and ensure the comprehensiveness of the analysis process.
[0027] S25: Filter with medium-speed quantitative filter paper and collect the filtrate, and wash it with hot water at 38±2℃ for multiple times; it can effectively remove residual solid particles and impurities, thereby obtaining a purer filtrate and avoiding interference of solid particles with subsequent measurements. At the same time, the washing step helps to extract the effective alkali ions in the sample as much as possible, ensuring that the alkali content in the filtrate represents the true state of the entire sample.
[0028] S26: Use phenolphthalein solution as an indicator and add additional hydrochloric acid solution to neutralize the filtrate; after the filtrate cools to room temperature, dilute to the required volume with distilled water. Neutralize the filtrate by adding hydrochloric acid to ensure that the pH of the solution is suitable for electrode measurement, and use standard quantitative steps (such as acid addition and water washing) to eliminate interference factors to obtain accurate alkali ion concentration data.
[0029] In the present invention, after 28 days of curing, the slurry of cement and admixtures may have hardened, and the bottle body may need to be destroyed to scrape off the slurry adhering to the bottle body. Therefore, considering instrument loss and accuracy, the present invention uses a sealable plastic bottle. In addition, the slurry of cement admixtures is highly alkaline and may corrode glass under experimental conditions. Therefore, the use of glass volumetric flasks should be avoided.
[0030] Preferably, in step S24, after water is added, the total amount in the experimental bottle is 40 times the mass of the sample to be tested.
[0031] Preferably, in step S26, hydrochloric acid is added to adjust the pH to neutral.
[0032] Preferably, during the test in step S3, the temperature difference between the sample and the standard solution does not exceed ±1°C.
[0033] As a preferred embodiment, in step S4, the effective alkali content wNa 2 The calculation formula of O(eq) is:
[0034]
[0035] Where: w Na2O(eq) is the effective alkali content; w K2O is the mass fraction of potassium oxide; w Na2O is the mass fraction of sodium oxide; 0.658 is the conversion coefficient of potassium oxide to sodium oxide.
[0036] As a preferred embodiment, in step S4, the potassium oxide content w K2O The calculation formula is:
[0037]
[0038] Where: w K2O is the mass fraction of potassium oxide; m 0 is the mass of the admixture sample, in g; MK is the molar mass of potassium, in g / mol; a(K + ) is the effective concentration of potassium ions in 500 mL of the test solution, in mol / L; 2.415 is the conversion coefficient of potassium to potassium oxide.
[0039] As a preferred embodiment, in step S4, the sodium oxide content w Na2O The calculation formula is:
[0040]
[0041] Where: w Na2O is the mass fraction of sodium oxide; m is the mass of the admixture sample, in g; M K is the molar mass of sodium, in g / mol; a(Na + ) is the effective concentration of sodium ions in 500 mL of the test solution, in mol / L; 2.696 is the conversion coefficient of sodium to sodium oxide.
[0042] Preferably, the number of tests for each measurement is set to two, and the measurement result is expressed as an average value of the two tests.
[0043] The beneficial effects of the present invention are:
[0044] The present invention utilizes the dissolution characteristics of alkali metal ions under specific environmental conditions and combines the sensitivity of the ion selective electrode method to measure the effective alkali content of mineral admixtures in a fast and simple way. Through the detection of the content of effective alkali, materials that may produce alkali-aggregate reaction can be screened out, thereby providing a basis for selecting appropriate admixtures in engineering applications and reducing the risks of concrete cracking, expansion, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 It is a block diagram of the absorption effect of the total alkali in the background technology of the present invention; DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0049] Table 1
[0050]
[0051]
[0052] Example 1
[0053] A method for quickly determining the effective alkali content in a mineral admixture for concrete comprises the following steps:
[0054] S1. Prepare mineral admixture samples in proportion, reduce the samples to about 10g by quartering method or reducer, sieve the samples through 80μm square hole sieve, remove metallic iron in the sieve residue with magnet, grind the sieve residue and pass it through 80μm square hole sieve to mix thoroughly, put it into sample bottle, seal and store; before analysis, dry the sample in (105±5)℃ oven to constant weight, put it into desiccator and cool it to room temperature for use.
[0055] S2. Weigh 5.0g (m0) of the mineral admixture to be tested and 2.0g of the reference cement, mix them evenly and transfer them to the experimental bottle. Use a pipette to add 10.0mL of water to the bottle, seal the bottle mouth with plastic film and shake the mixture. After standing for a while and a supernatant appears, gently rotate the experimental bottle to make sure there is no residue on the bottle wall. To avoid water loss, seal the bottle mouth with plastic film or tape, and place the sample bottle in a sealed container filled with water at the bottom, and then place it in an environment of (38±2)℃.
[0056] Open the vial on day 28, transfer all the contents to a mortar and grind into a uniform slurry (if the vial may need to be destroyed, care should be taken to avoid material loss and remove all solid materials from the vial fragments), then transfer to a beaker, add water to a total of 200 mL, and place at room temperature for 1 hour with attention to stirring. Filter through medium-speed quantitative filter paper into a 500 mL experimental bottle. At the same time, wash thoroughly with hot water at (38±2)℃ for 8 to 10 times.
[0057] The filtrate was neutralized with hydrochloric acid solution (1+3), with 1-2 drops of phenolphthalein solution as an indicator, and 5 mL of hydrochloric acid solution (1+3) was added additionally, the filtrate was cooled to room temperature, and the volume was made up with distilled water.
[0058] S3. Determination of potassium and sodium content: Determine the concentration of potassium and sodium alkali ions in the extract by ion selective electrode method; during the test, the temperature difference between the sample and the standard solution shall not exceed ±1°C;
[0059] S4. Calculation of results and determination of effective alkali: The measured alkali ion concentration is converted into the effective alkali content in the admixture, and finally the Na 2 O equivalent (%).
[0060] Among them, in step S4, the effective alkali content wNa 2 The calculation formula of O(eq) is:
[0061]
[0062] Where: w Na2O(eq) is the effective alkali content; w K2O is the mass fraction of potassium oxide; w Na2O is the mass fraction of sodium oxide; 0.658 is the conversion coefficient of potassium oxide to sodium oxide.
[0063] Specifically, the potassium oxide content w K2O The calculation formula is:
[0064]
[0065] Where: w K2O is the mass fraction of potassium oxide; m 0 is the mass of the admixture sample, in g; M K is the molar mass of potassium, in g / mol; a(K + ) is the effective concentration of potassium ions in 500 mL of the test solution, in mol / L; 2.415 is the conversion coefficient of potassium to potassium oxide.
[0066] Sodium oxide content Na2O The calculation formula is:
[0067]
[0068] Where: w Na2O is the mass fraction of sodium oxide; m is the mass of the admixture sample, in g; M K is the molar mass of sodium, in g / mol; a(Na + ) is the effective concentration of sodium ions in 500 mL of the test solution, in mol / L; 2.696 is the conversion coefficient of sodium to sodium oxide.
[0069] The number of tests for each measurement is stipulated to be two, and the measurement result is expressed as the average value of the two tests.
[0070] In the present invention, the verification work 1 determined the three mineral admixtures in cement and calcium hydroxide (Ca(OH) 2 ) as the activator. For mineral powder and metakaolin, when Ca(OH) 2 When used as an activator, the effective alkali content is significantly higher than that in cement; for silica fume, the effective alkali contents measured under the two activators are close, which is inconsistent with the release rules of the other two admixtures.
[0071] Table 2
[0072]
[0073] It can be seen that using cement as an activator can better simulate the environment in which mineral admixtures are located in actual concrete. Components such as silicates and aluminates contained in cement will undergo complex chemical reactions with admixtures, thereby affecting the release of effective alkali. The measured effective alkali content is closer to the performance in actual projects. At the same time, since the cement hydration process involves multiple chemical reactions, there is no need to distinguish between the alkali released by mineral admixtures and the alkali from the hydration reaction of cement itself. The measured effective alkali is close to the release of alkali in the actual concrete environment. In addition, the hydration reaction of cement usually takes a long time to reach a stable state, which is why the alkali content measured under cement stimulation is higher than Ca(OH) 2 Therefore, the measured effective alkali content should refer to the alkali content dissolved after the mineral admixture reacts with the benchmark cement for a certain age under experimental conditions. It is used to reflect the actual alkali dissolution of the mineral admixture in the cement-based system, which is closer to the actual environment.
[0074] On this basis, the present invention measures the total alkali content of three mineral admixtures, ground volcanic ash, fly ash, and ground tuff, with reference to Article 6.14 of "Cement Chemical Analysis Method" GB / T 176, and measures the effective alkali content according to this technical solution. The test results are shown in Table 3. By calculation, it is found that the effective alkali content of fly ash accounts for 13.42% of the total alkali content, which is close to the effective alkali value coefficient of fly ash in current specifications and projects of 1 / 6, which confirms the rationality of this method.
[0075] Table 3 Alkali content of various mineral admixtures
[0076]
[0077] In order to further verify the safety of the effective alkali content measured by this method, the effectiveness of mineral admixtures in inhibiting alkali-aggregate reaction was tested with reference to Appendix C of Railway Concrete TB / T 3275. The cement was P·Ⅰ cement with an alkali content of 0.8%; 30% of the mineral admixture and alkali-reactive aggregate were used to prepare mortar, and the 28d expansion rate of the mortar was used to verify whether the alkali in the admixture had potential harm to the concrete.
[0078] According to TB / T 3275 Appendix C C.7.3, when both the coarse and fine aggregates used in the project have alkali-silica reaction activity, and the length expansion rate of the specimens at 28 days of age measured by this method is less than 0.10%, the corresponding mineral admixtures and admixtures are evaluated to be effective in inhibiting the alkali-silica reaction of concrete. The test results are shown in Table 4.
[0079] Table 4 Test on effectiveness of mineral admixtures in inhibiting alkali-aggregate reaction
[0080]
[0081]
[0082] The alkali activity of the aggregate used is relatively large, and the alkali activity of the pure cement specimen is only 1.72kg / m 3 Under the condition of total alkali content, the expansion rate of 28d is as high as 0.30%. When 30% of volcanic slag and tuff are added, the total alkali content of the specimen reaches 3.04kg / m 3 and 8.08kg / m 3 , 28d expansion rates are 0.05% and 0.08% respectively. Especially when the total alkali content of tuff far exceeds the specification limit (3kg / m 3 ), there is still a significant alkali-aggregate reaction inhibition effect compared to the benchmark specimen (28d expansion rate is less than 0.10%). This shows that not all alkalis in mineral admixtures will have an adverse effect on the long-term performance and durability of concrete. As calculated in Table 2, the effective alkali content in the specimens prepared with volcanic slag and tuff is 1.34 kg / m 3 and 1.36kg / m 3 , which are lower than the effective alkali of the benchmark specimens, and therefore also show a lower 28d expansion rate, which confirms the scientificity and safety of this method.
[0083] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for rapidly determining the effective alkali content in mineral admixtures for concrete, characterized in that: The steps include: S1. Sample preparation: Prepare the mineral admixture sample and seal it after grinding and sieving. Before analysis, dry the sample to constant weight and cool it to room temperature for later use; S2. Preparation of extract: Prepare a slurry with the sample to be tested, reference cement and water in a mass ratio of 5:2:10, and after curing for 28 days, grind, dilute and filter to obtain the extract; S3. Determination of potassium and sodium content: Determine the concentration of potassium and sodium alkali ions in the extract by ion selective electrode method; S4. Calculation of results and determination of effective alkali: The measured alkali ion concentration result is converted into the effective alkali content in the admixture, and finally expressed as Na2O equivalent (%).
2. A method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 1, characterized in that: Step S1 specifically includes: S11: Prepare a mineral admixture sample in proportion, use a quartering method or a divider to reduce the sample to twice the prepared mass, and then sieve it through an 80μm square hole sieve; S12: Use a magnet to remove the metallic iron in the sieve residue, and grind the sieve residue again so that it all passes through a square hole sieve with a pore size of 80 μm to ensure uniformity; S13: Put the evenly ground sample into a sealed bottle for storage; S14: Before analysis, the sample is dried in an oven at (105±5)℃ to constant weight, then placed in a desiccator and cooled to room temperature for later use.
3. A method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 1, characterized in that: Step S2 specifically includes: S21: Weigh the test sample and reference cement in a mass ratio of 5:2, accurately record the sample mass to 0.0001g, mix them evenly and put them into the experimental bottle; S22: Add water twice the mass of the test sample into the experimental bottle, seal the bottle mouth and shake well to make sure there is no residue on the bottle wall; S23: Seal the test bottle, place the test bottle in a sealed container filled with water at the bottom, and then leave it at a temperature of 38±2℃ for 28 days; S24: After 28 days, the experimental bottle was opened and the entire contents were transferred to a mortar and ground into a homogeneous slurry, then transferred to a beaker, diluted with water, and left to stir for 1 hour; S25: Filter with medium-speed quantitative filter paper and collect the filtrate, and wash with 38±2℃ hot water for multiple times; S26: Use phenolphthalein solution as an indicator and add additional hydrochloric acid solution to neutralize the filtrate; after the filtrate is cooled to room temperature, dilute to the required volume with distilled water.
4. A method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 3, characterized in that: In step S24, after water is added, the total amount in the experimental bottle is 40 times the mass of the sample to be tested.
5. The method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 3, characterized in that: In step S26, hydrochloric acid is added to adjust the pH to neutral.
6. A method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 1, characterized in that: During the test in step S3, the temperature difference between the sample and the standard solution does not exceed ±1°C.
7. A method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 1, characterized in that: In step S4, the calculation formula of the effective alkali content wNa2O (eq) is: Where: w Na2O(eq) is the effective alkali content; w K2O is the mass fraction of potassium oxide; w Na2O is the mass fraction of sodium oxide; 0.658 is the conversion factor of potassium oxide to sodium oxide.
8. A method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 7, characterized in that: In step S4, the potassium oxide content w K2O The calculation formula is: Where: w K2O is the mass fraction of potassium oxide; m0 is the mass of the admixture sample, in g; M K is the molar mass of potassium, in g / mol; a(K + ) is the effective concentration of potassium ions in 500 mL of the test solution, in mol / L; 2.415 is the conversion coefficient of potassium to potassium oxide.
9. A method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 7, characterized in that: In step S4, the sodium oxide content w Na2O The calculation formula is: Where: w Na2O is the mass fraction of sodium oxide; m is the mass of the admixture sample, in g; M K is the molar mass of sodium, in g / mol; a(Na + ) is the effective concentration of sodium ions in 500 mL of the test solution, in mol / L; 2.696 is the conversion coefficient of sodium to sodium oxide.
10. The method for rapidly determining the effective alkali content in mineral admixtures for concrete according to claim 1, characterized in that: The number of tests for each measurement is specified to be two, and the measurement result is expressed as the average value of the two tests.
Citation Information
Cited By
Alkali consumption detection method under interaction of multi-element influence minerals in ore pulp
CN121049005A
A rapid screening and evaluation method and system for alkali-silicic acid reaction-inhibiting mineral admixtures
CN122677037A
Method and system for rapid screening and evaluation of alkali-silica reaction inhibiting mineral admixtures
CN122677037B